Mitochondrial dysfunction in heart failure and its therapeutic implications - Liu, Miaosen; Lv, Jialan; Pan, Zhicheng; Wang, Dongfei; Zhao, Liding; Guo, Xiaogang (Frontiers in Cardiovascular Medicine, 2022)
The ATP consumption in heart is very intensive to support muscle contraction and relaxation. Mitochondrion is the power plant of the cell. Mitochondrial dysfunction has long been believed as the primary mechanism responsible for the inability of energy generation and utilization in heart failure. In addition, emerging evidence has demonstrated that mitochondrial dysfunction also contributes to calcium dysregulation, oxidative stress, proteotoxic insults and cardiomyocyte death. These elements interact with each other to form a vicious circle in failing heart. The role of mitochondrial dysfunction in the pathogenesis of heart failure has attracted increasing attention. The complex signaling of mitochondrial quality control provides multiple targets for maintaining mitochondrial function. Design of therapeutic strategies targeting mitochondrial dysfunction holds promise for the prevention and treatment of heart failure.